Analisis Kepuasan Pengguna Jalan pada Akses Pendidikan di Kabupaten Toraja Utara - Bua', Rilva Toding; Sombolinggi, Azril Tangke (Universitas Ibn Khaldun, 2026)
This study aims to analyze the level of road user satisfaction on three access roads leading to educational areas in North Toraja Regency, namely the Rantepao–Palopo, Rantepao–Sa’dan–Batusitanduk, and Rantepao–Bolu corridors. Data were collected through questionnaires administered to 312 respondents who actively use these routes. The research instrument was tested using validity and reliability tests, and all variables were found to be valid and reliable. Descriptive analysis revealed variations in user perceptions across road classes. The Customer Satisfaction Index (CSI) was employed to measure overall satisfaction and indicated that the national road section achieved the highest satisfaction score, followed by the provincial and district roads. Multiple linear regression analysis was conducted to determine which service attributes significantly influenced user satisfaction. The results show that, for the provincial road, traffic flow, environmental comfort, and traffic management significantly influenced satisfaction, while for the district road, pavement condition and traffic flow were the primary determinants. Importance–Performance Analysis (IPA) was used to identify priority improvements for each road section, demonstrating that different strategies are needed depending on the characteristics of each road class and user perception. The findings of this study are expected to support decision-making and planning efforts aimed at improving road service quality in educational access areas in North Toraja.